(untitled) (NAU Journal of Library and Information Science, 2022)
This study is a comparative study of user education programmes in two selected universities in Anambra and Imo State. The study sought to investigate the effectiveness of library user instruction as a means of increasing library usage in academic libraries. The study was anchored on four stated objectives. The research design was descriptive survey design. Population of the study comprised 33,660 library staff and library users of Nnamdi Azikiwe University, Awka and Imo State University, Owerri. Purposive sampling technique was used to select a sample size of 756 respondents. The instrument for data collection was a structured questionnaire. Data collected was analyzed using frequency tables and simple percentage. Findings showed that traditional user education was the widely provided service by the libraries of NAU, Awka and IMSU, Owerri. The major user education method deployed to enhance effective utilization of information resources in the library include lecture method, presentation of handbook to students, use of library guide, library tour and compulsory teaching of General Studies two credit unit course. Major obstacles in teaching user education in the two institutions were inadequate learning environment and management delay in the commencement of user education program. Based on the findings, it was recommended that the libraries should strive to convert their patrons to habitual library users, train them on skills needed to retrieve library resources independently, and to help them sharpen their research skills.